Bạn chưa đăng nhập. Vui lòng đăng nhập để hỏi bài

Những câu hỏi liên quan
Nguyễn Thị Thanh Hoà
Xem chi tiết
kudo shinichi
23 tháng 10 2018 lúc 14:06

\(A=x^2\left(x+y\right)+y^2\left(x+y\right)+2x^2y+2xy^2\)

\(A=x^2\left(x+y\right)+y^2\left(x+y\right)+2xy\left(x+y\right)\)

\(A=\left(x+y\right)\left(x^2+2xy+y^2\right)\)

\(A=\left(x+y\right)\left(x^2+2xy+y^2\right)\)

\(A=\left(x+y\right).\left(x+y\right)^2\)

\(A=\left(x+y\right)^3\)

Dương Nguyễn Ngọc Khánh
Xem chi tiết
Mai Thành Đạt
5 tháng 6 2016 lúc 15:59

\(A=x^2\left(x+y\right)+y^2\left(x+y\right)+2xy\left(x+y\right)\)

\(\Leftrightarrow A=\left(x+y\right)\left(x^2+2xy+y^2\right)=\left(x+y\right)\left(x+y\right)^2=\left(x+y\right)^3\)

Trà My
5 tháng 6 2016 lúc 16:16

\(A=x^2\left(x+y\right)+y^2\left(x+y\right)+2x^2y+2xy^2\)

\(\Leftrightarrow A=\left(x^2+y^2\right)\left(x+y\right)+2xy\left(x+y\right)\)

\(\Leftrightarrow\left(x^2+2xy+y^2\right)\left(x+y\right)\)

\(\Leftrightarrow A=\left(x+y\right)^2\left(x+y\right)\)

\(\Leftrightarrow A=\left(x+y\right)^3\)

Sách Giáo Khoa
Xem chi tiết
Trần Thị Bích Trâm
20 tháng 4 2017 lúc 21:25

a) (x + 3)(x2 – 3x + 9) – (54 + x3) = (x + 3)(x2 – 3x + 32 ) - (54 + x3)

= x3 + 33 - (54 + x3)

= x3 + 27 - 54 - x3

= -27

b) (2x + y)(4x2 – 2xy + y2) – (2x – y)(4x2 + 2xy + y2)

= (2x + y)[(2x)2 – 2 . x . y + y2] – (2x – y)(2x)2 + 2 . x . y + y2]

= [(2x)3 + y3]- [(2x)3 - y3]


= (2x)3 + y3- (2x)3 + y3= 2y3

Tuyết Nhi Melody
20 tháng 4 2017 lúc 21:27

Bài giải:

a) (x + 3)(x2 – 3x + 9) – (54 + x3) = (x + 3)(x2 – 3x + 32 ) - (54 + x3)

= x3 + 33 - (54 + x3)

= x3 + 27 - 54 - x3

= -27

b) (2x + y)(4x2 – 2xy + y2) – (2x – y)(4x2 + 2xy + y2)

= (2x + y)[(2x)2 – 2 . x . y + y2] – (2x – y)(2x)2 + 2 . x . y + y2]

= [(2x)3 + y3]- [(2x)3 - y3]

= (2x)3 + y3- (2x)3 + y3= 2y3

khánh
Xem chi tiết
Buddy
Xem chi tiết
Hà Quang Minh
12 tháng 1 2024 lúc 23:23

a)

\(\begin{array}{l}\left( {2x - 5y} \right)\left( {2x + 5y} \right) + {\left( {2x + 5y} \right)^2}\\ = \left( {2x + 5y} \right)\left( {2x - 5y + 2x + 5y} \right)\\ = \left( {2x + 5y} \right).4x\\ = 2x.4x + 5y.4x\\ = 8{x^2} + 20xy\end{array}\)

b)

\(\begin{array}{l}\left( {x + 2y} \right)\left( {{x^2} - 2xy + 4{y^2}} \right) + \left( {2x - y} \right)\left( {4{x^2} + 2xy + {y^2}} \right)\\ = {x^3} + {\left( {2y} \right)^3} + {\left( {2x} \right)^3} - {y^3}\\ = {x^3} + 8{y^3} + 8{x^3} - {y^3}\\ = \left( {{x^3} + 8{x^3}} \right) + \left( {8{y^3} - {y^3}} \right)\\ = 9{x^3} + 7{y^3}\end{array}\)

Little Girl
Xem chi tiết
Hay Lắm
28 tháng 6 2016 lúc 7:17

1)  2xy2+x2y4+1=(xy2)2+2xy2.1+12=(xy2+1)2

2)

a)2(x-y)(x+y)+(x+y)2+(x-y)2=(x+y+x-y)2=(2x)2=4x2

b)(x-y+z)2+(z-y)2+2(x-y+z)(y-z)

=(x-y+z)2+(y-z)2+2(x-y+z)(y-z)

=(x-y+z+y-z)2

=x2

Nguyễn Thị Thanh Hoà
Xem chi tiết
Võ Thanh Nhung
23 tháng 10 2018 lúc 15:57

a)A=x3+x2y+y2x+y3+2x2y+2xy2

=x3+3x2y+3xy2+y3

A=(x+y)3

b)=3x2+2x+(x2+2x+1)-(4x2-25)=12

3x2+2x+x2+2x+1-4x2+25=12

4x+26=12

= >4x=6/13

= >x=6,5

Linh nguyễn
Xem chi tiết
Nguyễn Lê Phước Thịnh
1 tháng 1 2022 lúc 10:26

\(A=\dfrac{x^2-y^2+2y^2}{y\left(x-y\right)}\cdot\dfrac{-\left(x-y\right)}{x^2+y^2}+\dfrac{2x^2+2-2x^2+x}{2\left(2x-1\right)}\cdot\dfrac{-\left(2x-1\right)}{x+2}\)

\(=\dfrac{-1}{y}+\dfrac{-1}{2}=\dfrac{-2-y}{2y}\)

Buddy
Xem chi tiết
Hà Quang Minh
12 tháng 1 2024 lúc 22:07

\(\begin{array}{l}\left( {x - 2y} \right)\left( {{x^2} + 2xy + 4{y^2}} \right) + \left( {x + 2y} \right)\left( {{x^2} - 2xy + 4{y^2}} \right)\\ = {x^3} - {\left( {2y} \right)^3} + {x^3} + {\left( {2y} \right)^3}\\ = {x^3} - 8{y^3} + {x^3} + 8{y^3}\\ = 2{x^3}\end{array}\)